Alkene Transfer Hydrogenation with Alkaline-Earth Metal Catalysts - Bauer, Heiko; Thum, Katharina; Alonso, Mercedes; Fischer, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The alkene transfer hydrogenation (TH) of a variety of alkenes has been achieved with simple AeN(2) catalysts [Ae=Ca, Sr, Ba; N=N(SiMe3)(2)] using 1,4-cyclohexadiene (1,4-CHD) as a H source. Reaction of 1,4-CHD with AeN(2) gave benzene, NH, and the metal hydride species NAeH (or aggregates thereof), which is a catalyst for alkene hydrogenation. BaN2 is by far the most active catalyst. Hydrogenation of activated C=C bonds (e.g. styrene) proceeded at room temperature without polymer formation. Unactivated (isolated) C=C bonds (e.g. 1-hexene) needed a higher temperature (120 degrees C) but proceeded without double-bond isomerization. The ligands fully control the course of the catalytic reaction, which can be: 1)alkene TH, 2)1,4-CHD dehydrogenation, or 3)alkene polymerization. DFT calculations support formation of a metal hydride species by deprotonation of 1,4-CHD followed by H transfer. Convenient access to larger quantities of BaN2, its high activity and selectivity, and the many advantages of TH make this a simple but attractive procedure for alkene hydrogenation.
CRIS-Team WoS Importer:2019-04-12

Heteroleptic Heavier Alkaline Earth Metal Amide Complexes Stabilized by a Superbulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Thum, Katharina; Langer, Jens; Ballmann, Gerd; Pahl, Jürgen; Donaubauer, Wolfgang; Hampel, Frank; Harder, Sjoerd (Organometallics, 2019)
Heteroleptic alkaline earth metal (Ae = Ca, Sr, Ba) amide complexes with the superbulky β-diketiminate ligand DIPePBDI (CH[C(Me)N-DIPeP]2, DIPeP = 2,6-di-iso-pentylphenyl) have been prepared by direct deprotonation of DIPePBDI-H with either AeN′′2 or AeN′′2·(THF)2 (N′′ = N(SiMe3)2). Despite long reaction times of 5-14 days, this convenient one-step synthetic method has the major advantage that metal-pure products are obtained in generally quantitative yields. All (DIPePBDI)AeN′′ and (DIPePBDI)AeN′′·THF complexes are monomeric and stabilized by agostic metal···Me3Si and metal···iso-pentyl interactions. They are highly soluble in toluene and indefinitely stable toward ligand scrambling, even after 2 weeks at 140 °C. The same series with the smaller DIPPBDI ligand (CH[C(Me)N-DIPP]2, DIPP = 2,6-di-iso-propylphenyl) could, except for Ca, also be prepared by direct ligand deprotonation. The (DIPPBDI)CaN′′ and (DIPPBDI)CaN′′·THF complexes are stable toward ligand exchange up to 110 °C. Whereas THF-free (DIPPBDI)SrN′′ and (DIPPBDI)BaN′′ decompose at 50 and 20 °C, respectively, their THF adducts were found to be stable up to 60 °C. This is, however, strongly dependent on complex purity. Slight hydrolysis or contamination with KN′′ accelerates ligand scrambling. Therefore, partial hydrolysis and salt metathesis routes that involve KN′′ should be avoided when synthesizing heteroleptic complexes of the heavier Ae metals.
CRIS-Team Scopus Importer:2019-07-09

Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation

Lewis Acidic Cationic Strontium and Barium Complexes - Thum, Katharina; Martin, Johannes; Elsen, Holger; Eyselein, Jonathan; Stiegler, Lisa; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Lewis acidic (BDI)Ae+ cations of the heavier metals Sr and Ba, which are not stabilized by polar solvents, have been obtained by double deprotonation of (BDI)H2+ with either SrN’’2 or BaN’’2; BDI = HC[C(Me)N(DIPP)]2, DIPP = 2,6-diisopropylphenyl, Ae = alkaline earth, N’’ = N(SiMe3)2. Due to clathrate formation [(BDI)Ae+][B(C6F5)4−] could not be crystallized, but pyrene addition gave crystalline [(BDI)Ae+ ⋅ pyrene][B(C6F5)4−] which was structurally characterized for Ae = Mg, Ca, Sr, Ba. (R2N)Ae+ cations of the heavier metals Sr and Ba were obtained by reaction of Ae(NR2)2 with [Ph3C+][B(C6F5)4−] or [PhNMe2H+][B(C6F5)4−]. Following complexes were structurally characterized: [N’’Ba+ ⋅ (tol)2][B(C6F5)4−], [N*Sr+ ⋅ PhNMe2][B(C6F5)4−], [N*Ba+ ⋅ tol][B(C6F5)4−] and [N*Ba+ ⋅ C6H6][B(C6F5)4−]; tol = toluene and N* = N(SiiPr3)2. DFT calculations show that Sr⋅⋅⋅PhNMe2 coordination is preferred over Sr⋅⋅⋅toluene bonding. The (R2N)Ae+ cations can be used as Brønsted bases (reaction with (BDI)H gave (BDI)Ae+) and may be useful precursors for a variety of Lewis base-free RAe+ cations. DFT calculations, limited to monomeric model systems including B(C6F5)4− (ωB97XD/def2tzvpp//ωB97XD/def2svp), show that there is negligible electron transfer from the pyrene or toluene ligands to the Ae2+ cation. Electrostatic attraction originates from charge-induced polarization of the (Formula presented.) -electron density in the toluene and pyrene ligands.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Ab initio calculations; Arene coordination; Barium; Cations; Strontium

Retro-Diels-Alder decomposition of norbornadiene mediated by a cationic magnesium complex - Thum, Katharina; Pahl, Jürgen; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2021)
First evidence for the coordination of norbornadiene (nbd) and dicyclopentadiene (dcpd) with the main group metal Mg is provided by the crystal structures of adducts with cationic beta-diketiminate (BDI) Mg complexes. While the dcpd complex is thermally stable, [(BDI)Mg+center dot nbd][B(C6F5)(4)(-)] shows slow room temperature retro-Diels-Alder decomposition to give a complex with the cation (BDI)Mg(C5H5)Mg(BDI)(+).
CRIS-Team WoS Importer:2021-05-28

Unsupported Mg-Alkene Bonding - Thum, Katharina; Friedrich, Alexander; Pahl, Jürgen; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2020)
The first intermolecular early main group metal-alkene complexes were isolated. This was enabled by using highly Lewis acidic Mg centers in the Lewis base-free cations ((BDI)-B-Me)Mg+ and ((BDI)-B-tBu)Mg+ with B(C6F5)(4)(-) counterions ((BDI)-B-Me=CH[C(CH3)N(DIPP)](2), (BDI)-B-tBu=CH[C(tBu)N(DIPP)](2), DIPP=2,6-diisopropylphenyl). Coordination complexes with various mono- and bis-alkene ligands, typically used in transition metal chemistry, were structurally characterized for 1,3-divinyltetramethyldisiloxane, 1,5-cyclooctadiene, cyclooctene, 1,3,5-cycloheptatriene, 2,3-dimethylbuta-1,3-diene, and 2-ethyl-1-butene. In all cases, asymmetric Mg-alkene bonding with a short and a long Mg-C bond is observed. This asymmetry is most extreme for Mg-(H2C=CEt2) bonding. In bromobenzene solution, the Mg-alkene complexes are either dissociated or in a dissociation equilibrium. A DFT study and AIM analysis showed that the C=C bonds hardly change on coordination and there is very little alkene -> Mg electron transfer. The Mg-alkene bonds are mainly electrostatic and should be described as Mg2+ ion-induced dipole interactions.
CRIS-Team WoS Importer:2021-01-15